Study of Electroflotation to Harvest Cyclotella striata Biomass and Qualitative Analysis of Fatty Acids and Vitamin E from its Biomass - Dwi Puspitasari K S, Ratna
Harvesting microalgae from large scale cultures is one of problems in the biodiesel industry from microalgae. Electroflotation technique that agglomerate and concentrate microalgae on the surface is an alternative method to harvest microalgae rapidly, cheaply, and efficiently. The purpose of this research was to study the electroflotation method to harvest Cyclotella striata biomassa from large scale culture and to analyze fatty acid content and vitamin E from there dried biomass. Cells of C. striata were grown from a small scale indoor to a large scale outdoor and was harvested by the electroflotation method. Lipid C. striata was extracted by the modified Bligh?Dyer method and vitamin E was extracted by the saponification method followed by extraction. The results showed that C. striata cells grown in the 240 L culture indoor was prepared until the cell density reached 2,4×105 sel/mL. The C. striata cells were used as starting culture for cultivating cells in 1500 L culture outdoor for 8 d until the cell density reached 1×105 sel/mL. In a small scale electroflotation trial with a current density of 1,75 mA cm–2 and a measured voltage of 2 V, biomass of C. striata was harvesting from 700 mL culture for 10 min. From that result, a large scale electroflotation device equipped with 3 pairs of aluminium electrodes, with acrylic material that could accommodate up to 200 L of culture volume was designed and erected. The condition of large scale C. striata harvesting was similar to small scale harvesting. The efficiency of harvesting biomass of C. striata was 84%. The total energy and cost required for harvesting 1500 L culture of C. striata were 0.112 kWh and Rp 164, respectively. The GC?FID profile of lipid C. striata showed stearic acid as the highest fatty acid with a concentration of 18.0% (w/w). Yet vitamin E extracted from biomass and lipid C. striata could not be identified.